2022
DOI: 10.1371/journal.ppat.1010370
|View full text |Cite|
|
Sign up to set email alerts
|

The arginine deaminase system plays distinct roles in Borrelia burgdorferi and Borrelia hermsii

Abstract: Borrelia species are amino acid auxotrophs that utilize di- and tri- peptides obtained through their oligopeptide transport system to supply amino acids for replicative growth during their enzootic cycles. However, Borrelia species from both the Lyme disease (LD) and relapsing fever (RF) groups harbor an amino acid transport and catabolism system, the Arginine Deiminase System (ADI), that could potentially augment intracellular L-arginine required for growth. RF spirochetes contain a “complete”, four gene ADI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 101 publications
0
8
0
Order By: Relevance
“…Acetyl-CoA initiates a partial mevalonate pathway (BB_0685) essential for the synthesis of peptidoglycan precursor undecaprenyl phosphate ( 48 ). The arginine deiminase system produces ornithine (BB_0842) ( 49 ), which is the peptidoglycan crosslinking diamino acid ( 50 , 51 ). Again, matching recent experimental data, two glycerol-3-phosphate dehydrogenases were predicted: one using NADH as a cofactor (BB_0368) ( 52 ) and one using FADH (BB_0243) ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acetyl-CoA initiates a partial mevalonate pathway (BB_0685) essential for the synthesis of peptidoglycan precursor undecaprenyl phosphate ( 48 ). The arginine deiminase system produces ornithine (BB_0842) ( 49 ), which is the peptidoglycan crosslinking diamino acid ( 50 , 51 ). Again, matching recent experimental data, two glycerol-3-phosphate dehydrogenases were predicted: one using NADH as a cofactor (BB_0368) ( 52 ) and one using FADH (BB_0243) ( 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…For instance, the phospholipid synthases are predicted to be essential but could become nonessential due to passive uptake where the environment is abundant in phospholipids ( 55 ). The production of the cell wall diamino acid ornithine by arginine deiminase (BB_0841) is predicted essential here, but the enzyme has previously been inactivated both singly ( 49 ) and as part of a transposon library ( 57 ). Thus, the prediction of arginine deiminase essentiality is likely to reflect only the requirement for ornithine, which can be sourced either through the arginine deiminase system or by direct uptake from the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Richards et al have previously identified its role in Borrelia sp. growth, where it boosts intracellular L-arginine crucial for growth [ 79 ]. Inhibiting ADI has several advantages as a therapeutic strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Another important secondary source of energy in nutrient-poor environments (which is likely the case of salivary glands) could be the arginine dihydrolase (ADH) pathway, which occurs in many anaerobic bacteria, including spirochetes of the genus Treponema (Blakemore and Canale-Parola, 1976) and microaerophilic eukaryotes such as Giardia duodenalis (Brown et al, 1998). Interestingly, genes encoding all key components of the ADH pathway are present in RF Borrelia, whereas Lyme spirochetes possess only a truncated version of the pathway (Lescot et al, 2008;Lin et al, 2017;Richards et al, 2022), suggesting this could reflect the well-known differences in colonization strategies of the vector between these two groups of spirochetes (Schwan and Piesman, 2002). Albeit, the exact mechanisms behind such intertwined metabolism between the pathogen and its vector must be scrutinized in future studies.…”
Section: Feedingsmentioning
confidence: 99%